Influência de hormônios gonadais no eixo [ECA2/ANG(1-7)/Mas] encefálico para o controle da sede e apetite por sódio em ratos - Alves, Julio Cesar Santana (2013)
Sodium and water intake are important regulatory components of the hidromineral balance. In this context, human body regulates hidromineral imbalance through the neuro-immune-endocrine and behavioral response. Gonadal hormones are important players for the modulation of ingestive behaviors. The present study aimed to investigate the influence of male and female gonadal hormones in cerebral ECA2/ANG-(1-7)/Mas axis over the control of water sodium intake in rats. In this experiment, ovariectomized female rats were treated with estradiol benzoate (20μg/animal/day, sc; OVXE) or vehicle (sunflower oil; OVXV). Male rats underwent bilateral orchiectomy (ORQX) or sham surgery (SHAM). Guide cannulae were implanted into the right lateral ventricle for intracerebroventricular administration (icv) of drugs. We used angiotensin-converting enzyme type 2 (ACE2) activator, DIZE (diminazene of aceturate, 40 nmol / 2μl , icv ) or the antagonist of Ang-(1-7) Mas recetor, D-Ala7-ANG-(1-7) (A779, 10 nmol / 2μl, icv). The vehicle for both drugs was artificial cerebrospinal fluid (aCFS) administered in the same volume. For induction of thirst and sodium appetite, animals were subjected to hydrossaline depletion by administration of furosemide (20 mg / kg, sc) and access to distilled water and low sodium diet (corn ) for 24 hours. After microinjection of drugs, water and 0.3 M NaCl were reoffered and the ingested volume were recorded at the following 15, 30 , 60, 90 , 120, 180, 240 min and 24 h. Two-way analysis of variance was performed, followed by Bonferroni posthoc test when appropriate. The level of significance was p < 0.05. In females treated with vehicle or DIZE, sodium and water intake, as well as sodium preference index (SPI) did not differ between groups. However, OVXV ingested less water than OVXE when both were treated with A779 (p < 0.05). Twenty-four hours after reintroduction of fluids intake sodium ingestions was higher in OVXV than in OVXE when both received A779 (p<0.05). Similarly, OVXV rats showed greater preference for sodium when compared to OVXE, if both received icv injection of A779. Males ORQX microinjected with aCFS ingested more water than SHAM+aCSF. However, at 30 min, SHAM+DIZE male rats presented higher water intake when compared to their respective control. Up to 15 min after reintroduction of fluids, ORQX rats ingested less sodium than SHAM rats, regardless DIZE administration (p < 0.05). Water intake as well as SPI did not differ between groups in males undergoing A779 administrarion. However sodium intake was lower in ORQX+A779 than in ORQX+aCFS (p < 0.05) at 30, 60 , 90, 120 , 180 and 240 min after fluid presentation. Thus, we conclude that estrogen seems to exert inhibitory influences on sodium intake independent ECA2/ANG (1-7)/Mas activity. On the other hand, the male gonadal hormones act by raising intake for the regulation of salt intake shaft in the proposed protocol.